2021
DOI: 10.3389/fphys.2020.615961
|View full text |Cite
|
Sign up to set email alerts
|

Scale-Free Coupled Dynamics in Brain Networks Captured by Bivariate Focus-Based Multifractal Analysis

Abstract: While most connectivity studies investigate functional connectivity (FC) in a scale-dependent manner, coupled neural processes may also exhibit broadband dynamics, manifesting as power-law scaling of their measures of interdependence. Here we introduce the bivariate focus-based multifractal (BFMF) analysis as a robust tool for capturing such scale-free relations and use resting-state electroencephalography (EEG) recordings of 12 subjects to demonstrate its performance in reconstructing physiological networks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 114 publications
4
31
0
Order By: Relevance
“…This series of tests reveal the qualitative nature of bivariate multifractality, which is assessed independently from its quantitative changes in this study. The complete account of the testing procedure followed in this study was reported elsewhere ( Stylianou et al, 2021 ). We expanded the test yielding a distinction between extrinsic and intrinsic multifractality referred to as bivariate-univariate Hurst comparison.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This series of tests reveal the qualitative nature of bivariate multifractality, which is assessed independently from its quantitative changes in this study. The complete account of the testing procedure followed in this study was reported elsewhere ( Stylianou et al, 2021 ). We expanded the test yielding a distinction between extrinsic and intrinsic multifractality referred to as bivariate-univariate Hurst comparison.…”
Section: Methodsmentioning
confidence: 99%
“…The scale-free coupled dynamics were estimated with bivariate focus-based multifractal analysis (BFMF), introduced by Mukli and colleagues (Mukli et al, 2018). The applicability of BFMF for multifractal FC estimation was demonstrated previously (Stylianou et al, 2021). Here we only provide a summary of the method, while further details are found in the references mentioned above.…”
Section: Estimation Of Multifractal Functional Connectivitymentioning
confidence: 99%
See 2 more Smart Citations
“…There is an abundance of such bivariate methods that have been utilized in recent studies of physiological networks (Bashan et al, 2012;Bartsch et al, 2015;Zanetti et al, 2019), for a review see Schulz et al (2013). The relatively short time series (150 data points) were insufficient for adopting alternative bivariate measures such as symbolic transfer entropy (Dickten and Lehnertz, 2014;Lucchini et al, 2020), Granger causality (Faes et al, 2008) or measures of scale-free coupled dynamics (Stylianou et al, 2021) with suitable surrogate testing capable of identifying causal relationships (Schreiber and Schmitz, 1996). Adequate data representation is also necessary for using fractal models based on capturing spatio-temporal cross-dependencies between coupled physiological processes in order to identify physiological networks by utilizing fractional differencing operators (Xue et al, 2016;Bogdan, 2019).…”
Section: Discussionmentioning
confidence: 99%